Tumor burden and heterogenous treatment effect of apalutamide in metastatic castration-sensitive prostate cancer - Fukuokaya, Wataru; Mori, Keiichiro; Yanagisawa, Takafumi; Urabe, Fumihiko; Rajwa, Pawel; Briganti, Alberto; Shariat, Shahrokh F; Matsubara, Nobuaki; Kimura, Takahiro; Hirakawa, Akihiro (Cancer, 2025)
BACKGROUND: Investigation remains incomplete regarding potential variations in the effect of androgen receptor pathway inhibitors, including apalutamide, based on baseline tumor burden in patients with metastatic castration-sensitive prostate cancer (mCSPC). METHODS: The authors analyzed individual participant-level data from 1052 patients with mCSPC who were randomized in the TITAN trial (apalutamide vs. placebo, both with androgen-deprivation therapy). Outcomes included radiographic progression-free survival (PFS), second PFS (PFS2), and overall survival (OS). Multivariable Cox proportional hazards regression models, with and without restricted cubic splines, were used to determine the association between apalutamide benefit and bone metastasis count or visceral metastasis. Subgroup treatment effects were quantified based on inverse probability of treatment weighting-adjusted hazard ratios (HRs). RESULTS: Analysis using restricted cubic splines indicated that apalutamide provided less benefit for PFS2 and OS in patients with fewer bone metastases. The authors also found evidence of a heterogeneous effect of apalutamide on PFS2 and OS between patients with two or less bone metastases and those with three or more bone metastases. In patients who had two or less bone metastases, there was no evidence of a benefit from apalutamide for radiographic PFS (HR, 0.65; 95% confidence interval [CI], 0.35-1.22), PFS2 (HR, 1.18; 95% CI, 0.66-2.12), or OS (HR, 1.05; 95% CI, 0.60-1.83). No evidence of an association was noted between visceral metastasis and apalutamide benefit. CONCLUSIONS: The addition of apalutamide to androgen-deprivation therapy may provide less benefit in patients with mCSPC who have fewer bone metastases. Counting baseline bone metastases may help identify optimal candidates for apalutamide treatment of mCSPC. CLINICAL TRIALS REGISTRATION: NCT02489318 PLAIN LANGUAGE SUMMARY: In an analysis of individual participant data from a trial (the TITAN trial) in patients with metastatic (spreading) castration-sensitive prostate cancer, treatment intensification based on the addition new drugs to standard androgen-deprivation therapy (ADT) was analyzed and compared with the effects in patients who received only standard ADT. Compared with ADT alone, the survival benefit of adding the new drug apalutamide to standard ADT varied according to the number of bone metastases, but no association was observed between the spread of cancer to soft tissues and organs and a survival benefit from adding apalutamide. The results indicate that counting the number of bone metastases may help identify which patients with metastatic castration-sensitive prostate cancer are optimal candidates for treatment intensification with the addition of apalutamide to standard ADT.
Keywords: doba přežití bez progrese choroby; mužské pohlaví; nádory kostí; Male; senioři; thiohydantoiny; výsledek terapie; nádory prostaty rezistentní na kastraci; Humans; castration‐sensitive prostate cancer; Thiohydantoins; apalutamide; Prostatic Neoplasms, Castration-Resistant; lidé; metastázy nádorů; Middle Aged; Tumor Burden; lidé středního věku; tumor burden; antagonisté androgenů; Progression-Free Survival; Treatment Outcome; heterogeneity in treatment effect; Neoplasm Metastasis; antagonisté androgenních receptorů; Bone Neoplasms; Aged; Androgen Antagonists; prostate cancer; Androgen Receptor Antagonists